Refractory high entropy alloys: CrMoNbTiVWZr and AlxCryNbMoTiVzZry(x = 0, 0.6;y = 0.3, z = 0, 0.6). (November 2018) - Poletti, M.G.; McCaughey, C.M.; Fiore, G.; Goodall, R.; Battezzati, L.
Abstract: Four potential High Entropy Alloys, CrMoNbTiVWZr, Cr 0.3 NbMoTiZr 0.3, Cr 0.3 NbMoTiV 0.6 Zr 0.3 and Al 0.6 Cr 0.3 NbMoTiV 0.6 Zr 0.3 have been designed using the indications provided by atomic radius and electronegativity mismatch parameters. Alloys were synthesized by arc melting and characterized in the as-cast state and after heat-treatment by X-ray Diffraction and Scanning Electron Microscope experiments. In the as-cast state all alloys have dendritic microstructure, although with varied shapes of dendrites, accompanied by a cubic Laves phase and an hcp phase in the region between the dendrites. After annealing at 1350 °C for 3 h it is shown that only non-equimolar compositions are constituted of bcc high entropy phase complying with the requirements for defining them as HEAs, with a small amount of secondary phases which help in providing high hardness. Highlights: New High Entropy Alloys designed: CrMoNbTiVWZr and Al x Cr y NbMoTiV z Zr y (x = 0, 0.6;y = 0.3, z = 0, 0.6). Method to tailor composition while retaining solid solution phases verified. Microstructure homogenization of cast alloy obtained with proper heat treatment.